1997
DOI: 10.1111/j.1365-2621.1997.tb12229.x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanism of Lipid Oxidation following High Pressure Treatment in Pork Fat and Meat

Abstract: Addition of citric acid (0.02%) inhibited the increased rate of lipid oxidation found in rendered pork fat following pressure treatment (650-800 MPa). This indicated that transition metal ions were probably released from complexes and became available to catalyze lipid oxidation in the pressure treated fat. In minced pork and washed fibers citric acid was less effective in inhibiting oxidation in pressure treated samples because of its pH lowering effects. However, the less acidic ethylenediaminetetraacetic-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(54 citation statements)
references
References 22 publications
2
51
0
1
Order By: Relevance
“…Angsupanich and Ledward (1998) reported that treatment at -400 MPa had little effect on lipid oxidation in cod muscle, but that a significant increase in oxidation was seen following treatment at higher pressures. Cheah and Ledward (1997) and Angsupanich and Ledward (1998) proposed that the major reason for the acceleration of lipid oxidation by HP treatment was an increase in free metal ion (Fe and Cu) content of minced pork and cod muscle. It is possible that the change in colour of oyster tissue and oyster adductor muscle may be linked to lipid oxidation.…”
Section: Effect Of Hp Treatment On Colour Of Oystersmentioning
confidence: 99%
“…Angsupanich and Ledward (1998) reported that treatment at -400 MPa had little effect on lipid oxidation in cod muscle, but that a significant increase in oxidation was seen following treatment at higher pressures. Cheah and Ledward (1997) and Angsupanich and Ledward (1998) proposed that the major reason for the acceleration of lipid oxidation by HP treatment was an increase in free metal ion (Fe and Cu) content of minced pork and cod muscle. It is possible that the change in colour of oyster tissue and oyster adductor muscle may be linked to lipid oxidation.…”
Section: Effect Of Hp Treatment On Colour Of Oystersmentioning
confidence: 99%
“…Catalysis of lipid oxidation seems to take place during pressurization and has been related to the release of non-haem iron and membrane damage. Cheah and Ledward [24,25] reported that the effect of HPP on oxidative stability of lipids in pork meat depends on the applied pressure, with a value between 300 and 400 MPa constituting the critical pressure to induce catalysis. They also reported that denatured forms of proteins play an important role in catalysing lipid oxidation.…”
Section: Effect Of Hpp On Lipid Oxidationmentioning
confidence: 99%
“…Carlez et al [23] reported that meat discolouration in pressure-processed meat was due to the following: (1) a whitening effect due to myoglobin denaturation and/or to haem displacement or release and (2) oxidation of the ferrous myoglobin to ferric myoglobin above 400 MPa. Cheah and Ledward [25] improved the colour stability with the application of pressure of 80-100 MPa for 20 min, as measured by the rate of formation of metmyoglobin in beef muscles post-slaughter. However, pressure treatment of these muscles at 7-20 days post-slaughter did not improve their colour stability.…”
Section: Effect Of Hpp On Colourmentioning
confidence: 99%
“…Some researchers have found that raw and cooked fat are very susceptible to lipid oxidation during processing and subsequent storage 5 . Due to the high content of lipid in Altay sheep tail fat, it is very easy to be affected by the outside environment and lead to corruption.…”
mentioning
confidence: 99%